Application of electrical resistivity tomography for mapping gold mineralization potential in Iperindo, Ilesha schist belt, southwestern Nigeria - OlakunleOsinowo, Olawale; Kehinde Usman, Ahmed; Allen Omitoogun, Ayotunde (International Journal of Advanced Geosciences, 2020)
This study applied Electrical Resistivity Tomography geophysical investigation technique to evaluate the gold mineralization potential of Iperindo in Ilesha Schist Belt, southwestern Nigeria, where commercial exploitation capable of generating revenue and employment for the inhabitants has been challenged by lack / inadequate subsurface geological/geophysical information. The filtered and inverted electrical resistivity data acquired through five (5) 336 m long E â€“ W trending profiles, established 10 m apart from each other, delineate isolated near surface but thick (> 30 m) low resistivity zones, especially at the eastern and western ends of the study area. Some of the delineated low resistivity zones (3 â€“ 200 ð›€m) present vertical sharp edges, likely created by vertical faults that flank the zones on both sides. The low resistivity of these zones could be attributed to the occurrence of conductive material such as gold and associated base metals which probably exist in pegmatitic veins within the zones.Â Â Â